How to research - Blaxter, Loraine; Hughes, Christina; Tight, Malcolm (Buckingham : Open University Press, 1996)
This book is about: Thinking about research; Getting started; Thinking about methods; Reading for research; Managing your project; ...
Keywords: Research; Methodology; Research -- Methodology